(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The purpose of this study was to evaluate female students’ attitudes and understanding of cervical cancer screening. It was decided to use a cross-sectional study design. Selected from among the 100 female students in each of the five (5) faculties were total enumeration sampling approaches. A questionnaire that was given to the respondent served as the tool for gathering data. The statistical program SPSS version 21 was used to code, enter, and analyze the data that was obtained. Data was presented using frequency tables and percentages, and descriptive statistics were utilized to analyse it. This study found that a significant portion of female students knew about cervical cancer screening, but had negative attitudes about their preparation and willingness to undergo the screening. The study’s findings led researchers to the conclusion that respondents’ knowledge about cervical cancer screening was generally high at 80 (80.0%). To get a cervical cancer screening, the majority of respondents 65 (65.0) indicated some reluctance based on their attitude. Acceptability, accessibility, gap between screenings, and screening advertising are a few examples of factors that can affect participation rate. The study made the recommendation that cervical cancer screening must be effectively communicated to female students, particularly through the use of behavior change communication strategies where a supportive environment is offered to break down barriers and allay the fears of the female students. There is a need to design health communication interventions that would encourage tertiary level students to translate their knowledge into positive health action against cervical cancer. This can be accomplished by gradually enlightening the public. Female students should be encouraged to view screening as an opportunity to enhance effective prevention of cervical cancer rather than as an attempt to identify diseases in them.